Towards Transformation Rule Composition - Syriani, Eugene; Asztalos, Mark; Wimmer, Manuel; Kessentini, Marouane (Electronic Communications of the EASST, 2011)
Many model transformation problems require different intermediate transformation steps. For example, platform-specific models (PSM) are often generated from platform-independent models (PIM) by chains of model transformations. This requires the presence of several intermediate meta-models between those of the PIM and the PSM. Thus, most of the effort is needed to define a transformation mechanism for each intermediate step. The solution proposed in this paper is to investigate whether it is possible to generate a single transformation from a chain of transformations, solely involving the initial PIM and final PSM meta-models. The presented work focuses on the composition of transformations at the rule level. We apply the automatic procedure for composing rules in the context of the evolution of the Enterprise Java Beans (EJB) language, transforming UML models into EJB 2.0 models and then to EJB 3.0 models.